2012
DOI: 10.7314/apjcp.2012.13.11.5581
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Computed Tomography Manifestations of Thymic Epithelial Tumors and the WHO Pathological Classification

Abstract: Objective: To explore the relationship between computed tomography (CT) manifestations of thymoma and its WHO pathological classification. Methods: One hundred and five histopathologically confirmed cases were collected for their pathological and CT characteristics and results were statistically compared between different pathological types of thymoma. Results: Tumor size, shape, necrosis or cystic change, capsule integrity, invasion to the adjacent tissue, lymphadenopathy, and the presence of pleural effusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 20 publications
4
19
0
4
Order By: Relevance
“…The lobulation rate is between 60% and 89% based on previous study23. Focusing on common CT manifestation parameters, we detected that size, boundary, capsule, homogeneity, septa, necrotic or cystic change, pleural effusion, lymphadenopathy, and invasion of adjacent tissues demonstrated significant differences among the 6 TETs subtypes, which confirms previous findings1415161718. However, there was no significant difference for tumor shape among the different pathological types of TETs (P = 0.206), which is inconsistent with previous studies1415161718.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The lobulation rate is between 60% and 89% based on previous study23. Focusing on common CT manifestation parameters, we detected that size, boundary, capsule, homogeneity, septa, necrotic or cystic change, pleural effusion, lymphadenopathy, and invasion of adjacent tissues demonstrated significant differences among the 6 TETs subtypes, which confirms previous findings1415161718. However, there was no significant difference for tumor shape among the different pathological types of TETs (P = 0.206), which is inconsistent with previous studies1415161718.…”
Section: Discussionsupporting
confidence: 89%
“…However, current CT scan cannot effectively differentiate different WHO pathological classifications14. Although several studies have suggested that CT manifestation parameters (tumor size, shape, necrosis or cystic change, capsule integrity, invasion to the adjacent tissue, lymphadenopathy, the presence of pleural effusion, etc) demonstrated significant differences in different TETs types1415161718192021, up to date these parameters could not effectively predict WHO classifications with satisfactory sensitivity and specificity. Besides, the sample sizes of these studies are relatively small, which limits their ability to provide a precise answer for our research question of interest.…”
mentioning
confidence: 99%
“…Conversely, only the presence of lobulated contours was equally distributed in both patient populations, while the residual CT data (such as necrotic or cystic component and calcifications) were different. Studies by Sadohara et al ., Jeong et al ., and Liu et al . focused on the differentiation among low and high‐risk thymoma, and thymic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…but it cannot accurately differentiate between different subtypes of WHO classifications (11)(12)(13)(14)(15)(16)(17)(18). The importance of CT findings to distinguish early and late clinical stages has already been described (1)(2)(3)(4)16).…”
Section: Thoracic Imaging: Diffusion-weighted Mr Imaging In Thymic Epmentioning
confidence: 96%